Sosialisasi VRF Route Corridor dan Flight Training Area kepada Masyarakat Penerbangan Federasi Aero Sport Indonesia (FASI) di Banyuwangi - Hariri, Ahmad (TEKIBA : Jurnal Teknologi dan Pengabdian Masyarakat, 2021)
Abstract – Aero Sport is a type of aerospace sport that grew together with the world of aviation, both civil and military. The perpetrators of this extreme sport must understand flying safety procedures to minimize the dangers and risks faced. To bring up the growth of interest in aerospace sports, it is necessary to carry out ongoing socialization and education efforts for the pilot community who are members of the Indonesian Aero Sport Federation (FASI) or other general public. This PKM activity is carried out as part of a series of community service activities for the Banyuwangi API Institution. The activity was carried out for 3 days with participants from the FASI pilot community, APIB cadets, and Banyuwangi scout students. The results of the activity showed a positive response to the interest in aerospace sports which was disserted with the establishment of a DATC organization under the auspices of APIB. From this activity, the pilot community gained an understanding of the VRF Route Corridor and the Flight Training Area for the Banyuwangi API. Keyword: Aero Sport, Community Service, API Banyuwangi, FASI.